Design of gel structures in water and oil phases for improved delivery of bioactive food ingredients. Issue 10 (30th May 2020) - Mao, Like; Lu, Yao; Cui, Mengnan; Miao, Song; Gao, Yanxiang
Abstract: Gels are viscoelastic systems built up with a liquid phase entrapped in a three-dimensional network, which can behave as carriers for bioactive food ingredients. Many attempts have been made to design gel structures in the water phase (hydrogels, emulsion gels, bigels) or oil phase (organogels, bigels) in order to improve their delivery performances. Hydrogels are originated from proteins or polysaccharides, which are suitable for the delivery of hydrophilic ingredients. Organogels are mainly built up with the self-assembling of gelator molecules in the oil phase, and they offer good carriers for lipophilic ingredients. Emulsion gels and bigels, containing both aqueous and oil domains, can provide accommodations for lipophilic and hydrophilic ingredients simultaneously. Gel structures (e.g. rheology, texture, water holding capacity, swelling ratio) can be modulated by choosing different gelators, modifying gelation techniques, and the involvement of other ingredients (e.g. oils, emulsifiers, minerals, acids), which then alter the diffusion and release of the bioactive ingredients incorporated. Various studies have proved that gel-based delivery systems are able to improve the stability and bioavailability of many bioactive food ingredients. This review provides a state-to-art overview of different gel-based delivery systems, highlighting the significance of structure–functionality relationship, to provide advanced knowledge for the design of novel functional foods.